Improving the physical fitness of students on the basis of an elective course on the crossfit system - S.I. Filimonova,; A.S. Grachev,; D.E. Egorov,; D.V. Shcherbin, (Theory and Practice of Physical Culture, 2023)
Objective of the study was to increase the level of physical fitness of students by introducing classes based on the CrossFit system into the educational process of elective courses in physical culture and sports. Methods and structure of the study. For scientific research, an experimental group (EG) was formed, including 77 people (47 boys and 30 girls) with an average age of 18.9 ± 1.4 years, and a control group (CG), consisting of 77 people (33 boys and 44 girls) with an average age of 19.4±1.2 years. During the 2021-2022 academic year, the EG was trained according to the methodology using the CrossFit system. To assess its effectiveness, in September 2021 and May 2022, control standards from the VFSK GTO - stage VI for men and women were adopted. Results and conclusions. Comparative analysis of the results showed significant improvements in strength and aerobic endurance in men and women from the EG, while in the CG the results remained at the same level or slightly decreased. The obtained data testify to the positive impact of CrossFit classes on some components of students' physical fitness.